Reason and Revelation in the Thought of Saadiah Gaon - Abd. Malek, Khaldun Munip (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
Saadya bin Joseph (882-942), also known as Saadiah Gaon, was born in Fayyum, Upper Egypt. He was the first philosopher of Judaism to write systematic works. He was also a pioneering exegete, grammarian, lexicographer, liturgist, and chronologist. His early years were spent in Egypt, and apparently it was there he began corresponding with Isaac Israeli of Kairouan (c.855-c.955), the physician philosopher who, due partly to the influence of al-Kindi, initiated the tradition of Neoplatonic philosophy among Arab speaking Jews. It was also during his youth that he became involved in a series of disputations with the Karaites, a sect that prided themselves on their rejection of the Talmud and their acceptance of the Bible as the only legitimate source of revelation. The controversy that emerged from disagreement between Saadya and the Karaites were symptomatic of later events in his life, where his erudition and learning, as well as his critical intellect, would lead him into further persecution, enmity, and eventually, exile.